Joint pricing and power allocation for multibeam satellite systems with dynamic game model - Li, Feng (2019)
Multibeam satellite systems (MSS) enable transmission flexibility and spatial diversity while efficiently reusing the scarce spectrum resource. However, as spectrum reuses tend to introduce co-channel interference, MSS need to address power allocation and interference management carefully. In this paper, we tackle the joint interference pricing and power allocation problems of MSS by formulating the underlying resource allocation problem as a dynamic game model - the Stackelberg model. In our proposed scheme, a fresh satellite user will be charged according to its interference on the satellite system. MSS can dynamically adjust the interference price in order to make a tradeoff between intercell interference and operating profit. Meanwhile, for the satellite user, an equilibrium power allocation should be ascertained in response to the MSS's pricing. A novel market-based solution is proposed for interference management in MSS by introducing an elastic price mechanism. The Nash equilibrium for interference pricing and its iterative convergence for power allocation have further been proven. Numerical results are provided to evaluate the impact of different prices on the utility functions of both MSS and satellite users.